Avaliação das alterações na composição corporal de ratos tratados cronicamente com dexametasona e submetidos ao exercício resistido - Siqueira, Andressa Pâmela Pires de (2018)
The physical exercise is fundamentally important for the individual's life and health. The physical inactivity and/or low physical conditioning, on the other hand, has been considered one of the risk factors of premature mortality with deleterious effects similar to other deseases, such as high blood pressure and dyslipidemia. Among the different types of exercises the resisted exercise (anaerobic) promotes positive changes in bodily composition, treatment and prevention of deseases in several populations, as well as improvement in physical aptitude. This modality is characterized by muscle tension (possessing or not articulated movement) against some resistance to muscle action. In that sense, na experiment was carried out with forty wistar rats divided into four groups weighing between 250g-300g. They were submitted to resisted exercise and it was administrated glucocorticoid (dexomenthasone 0,2 mg/kg/day). It was possible to observe that there was no significant difference in the rats' body weight under medication and trained. A gain in soleus muscle mass was evidenced after the training period (28,33% and 25,29% for the trained and dexa-trained control groups, respectively), as well as the decrease in perigonous fat (26,6% and 24% for the trained and dexa-trained control groups, respectively). The results suggest that resisted exercises improve the skeletical musculature and consequently the decrease in the fat mass. Moreover, the main finding of this study was the soleum muscle hypertrophy, which needs more studies that clarify such mechanism.